(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
In order to improve the security of secret image transmission, using the property of the chaotic sequence in the encryption algorithm, a block image encryption scheme based on Logistic and Henon composite chaotic system is presented. The image encryption algorithm from two aspects that the pixel grayscale value and pixel position through two different chaotic sequences transform of the Logistic and Henon. At first, Logistic chaotic sequence is applied to the scrambling operation on the pixel position matrix. Then the pixel values of blocked images are scrambled based on Henon chaotic sequence. The experiments show that the algorithm has good encryption effect, and has better robustness to crop or noise attack. The cross correlation of encrypted image are decreased and the transport security is improved, the result shows that the project is effective.